Powerful eaudiobook - Roberts, Lauren (Powerless Trilogy, 2024)
#1 New York Times Bestseller Set during Powerless , fan-favorite Adena gets a story all her own in this unique special edition of the runaway hit! This deluxe format includes sprayed stenciled edges, decorative endpapers, case stamping, ribbon marker, and Powerless trivia and quizzes! Adena and Paedyn have always been inseparable. Fate brought them together when they were young, but friendship ensured they would always protect each other and the home they built in the slums of Loot. But now Paedyn—an Ordinary—has been selected for the Purging Trials, which means almost certain death. Now alone in Loot, Adena must fend for herself. After attempting to steal, she's rescued by a mysterious man from the market. Mak's shadowy past and secretive power set him apart from the other low-level Elites of Loot. And as the pair team up to see their loved ones before the Trials, the quest tests their loyalty, their love, and their lives.